2008
DOI: 10.1159/000122111
|View full text |Cite
|
Sign up to set email alerts
|

Human Leukocyte Antigen <i>DRB1</i> Alleles Predict Risk and Disease Progression of Immunoglobulin A Nephropathy in Han Chinese

Abstract: The role of human leukocyte antigen (HLA) class II polymorphisms in the pathogenesis and progression of primary immunoglobulin A nephropathy (pIgAN) is unclear. This study aimed to explore the relationship of HLA-DRB1 alleles with the susceptibility and disease progression of pIgAN in Han Chinese. A PCR-based genotyping technique was used to detect HLA-DRB1 alleles in 139 patients with pIgAN and 143 healthy subjects. A total of 37 HLA-DRB1 alleles were detected, of which 30 were found in pIgAN patients and 29 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 49 publications
2
12
0
Order By: Relevance
“…HLA-DR/DQ, coding for MHC II molecules and involved in antigen presentation, was detected by all five GWAS regardless of racial origins (7)(8)(9)(10)(11). HLA-DRB1 classic alleles have been reported to be related to disease progression in a Chinese IgA nephropathy cohort (37). In this study, we determined patients carrying rs2856717-T had an increased risk for disease progression.…”
Section: Discussionmentioning
confidence: 88%
“…HLA-DR/DQ, coding for MHC II molecules and involved in antigen presentation, was detected by all five GWAS regardless of racial origins (7)(8)(9)(10)(11). HLA-DRB1 classic alleles have been reported to be related to disease progression in a Chinese IgA nephropathy cohort (37). In this study, we determined patients carrying rs2856717-T had an increased risk for disease progression.…”
Section: Discussionmentioning
confidence: 88%
“…It is known that IgA antibody‐mediated immune response is T‐cell dependant, and the HLA class‐II products coded by DP, DQ, and DR genes affect antigen presentation to particular T cells . Reports from Hong Kong, Taiwan, Guangdong, and Sichuan have revealed HLA ‐family genetic variants to be associated with the genetic susceptibility of IgAN or a special subgroup of IgAN . It has already been reported that there is an association between HLA‐DRB1 polymorphisms and IgAN in the Han Chinese; HLA‐DRB1 * 140501 confers susceptibility, while HLA‐DRB1 * 070101 confers resistance.…”
Section: Discussionmentioning
confidence: 99%
“…HLA-DRB1*140501 was reported to be a susceptible allele, and HLA-DRB1*070101 was reported to be a resistant allele. HLA-DRB1*030101 may serve as a predictor of disease progression and renal damage of primary IgAN in Han Chinese [ 29 ]. However, previous studies did not substantiate the conclusion that HLA-DRB1 was significantly associated with IgAN because a small number of samples were included in these studies and there was no association between the HLA-DR antigen and primary IgAN in Taiwanese Chinese [ 20 ].…”
Section: Discussionmentioning
confidence: 99%